Cyanobacteria-Dominated Phytoplankton in the Oligotrophic South China Sea Maintain Photosynthetic Potential Despite Diurnal Photoinactivation of PSII - Yi, Xiangqi; Zhang, Di; Sun, Jiazhen; Beardall, John; Gao, Kunshan (Frontiers in Marine Science, 2021)
In the warm, oligotrophic oceans, phytoplankton frequently experience high light exposure and must compete for a potentially limited nutrient supply. Additionally, the light regimes are dynamic in view of the diel solar cycle, weather conditions and depth. Dealing with these challenges is critical to their survival. Here, we explored, using active chlorophyll a fluorescence, the photophysiological responses of cyanobacteria-dominated phytoplankton assemblages to intra-day variations in the light regime in the oligotrophic South China Sea (SCS). Experiments were conducted at three stations (SEATS, DC2 and DC6) where phytoplankton communities were dominated by Prochlorococcus and Synechococcus, and environmental conditions were similar except for daytime light conditions. We found that, at each station, the maximum quantum yield of PSII (Fv/Fm) at dawn was as high as 0.5, although concentrations of both dissolved inorganic nitrogen and soluble reactive phosphate were below the detection limits. Subsequently, diurnal patterns of Fv/Fm diverged between stations. At stations DC2 and DC6, we observed significant drops (25 - 48%) of Fv/Fm around midday, coinciding with the incident solar photosynthetically active radiation (PAR) reaching over 2000 μmol quanta m-2 s-1, but Fv/Fm was nearly stable at SEATS where the daily maximal PAR was less than 1000 μmol quanta m-2 s-1. Further analysis suggests that the midday drops in Fv/Fm at DC2 and DC6 were a consequence of high light-induced PSII photoinactivation. On the other hand, we found that the patterns of diurnal variation in maximum relative electron transport rate (rETRmax) presented as being unimodal with a peak around midday at all three stations. Furthermore, we determined that the diurnal pattern of rETRmax was mainly controlled by the extent of photochemical quenching (qP). Considering that rETRmax reflects the photosynthetic potential and that qP is indicative of the redox status of electron carriers downstream of PSII and the activity of electron-consuming mechanisms, our results indicate that, in the oligotrophic SCS, through increasing the activity of the electron-consuming mechanisms (high qP), phytoplankton are able to maintain their midday photosynthetic potential (high rETRmax) even with a degree of PSII photoinactivation (low Fv/Fm).